Hybrid Treatment of Extracranial Carotid Artery Disease. (August 2017) - Bozzay, Joseph; Broce, Mike; Mousa, Albeir Y.
Objective: High-degree stenosis of both innominate (IA) or left common carotid artery (CCA) and carotid bifurcation is uncommon but still represents a significant challenge to interventionists in many aspects including techniques, timing, and priority. There are several strategies for intervention that have been reported in the literature. A well-described, less-invasive strategy for extracranial tandem carotid lesions is concomitant carotid endarterectomy (CEA) with retrograde carotid angioplasty and stenting (CAS). In this study, we examine intermediate-term outcomes of this hybrid procedure and review other described treatments. Methods: Electronic medical records of all patients who underwent hybrid (ostial CAS and CEA) procedures in a tertiary center over the last 10 years were reviewed. High-degree stenosis of the IA or CCA was defined according to North American Symptomatic Carotid Endarterectomy Trial criteria. Results: A total of 6 patients were identified. The population included 4 males and 2 females with a median age of 65 years. Five patients were symptomatic and all had stenosis >75% by angiography. Five of the patients underwent left CEA with proximal stenting and one patient underwent right-sided CEA with proximal stenting. Combined 30-day mortality and stroke rate was 0%. No restenosis, stroke, heart attack, or death occurred during a follow-up range of 1 to 36 months (mean 12.8 months, median 7.8 months). Conclusion: The combined CEA with retrograde stenting for tandem extracranial lesion procedure is safe and feasible, with adequate intermediate-term outcomes consistent with the recent literature.